On virtue ethics - Hursthouse, Rosalind (Oxford University Press, 1999)
Virtue ethics is perhaps the most important development within late 20th-century moral philosophy. Rosalind Hursthouse presents an exposition and defence of her neo-Aristotelian version of virtue ethics.